2014
DOI: 10.1371/journal.ppat.1004291
|View full text |Cite
|
Sign up to set email alerts
|

Plasmacytoid Dendritic Cells Suppress HIV-1 Replication but Contribute to HIV-1 Induced Immunopathogenesis in Humanized Mice

Abstract: The role of plasmacytoid dendritic cells (pDC) in human immunodeficiency virus type 1 (HIV-1) infection and pathogenesis remains unclear. HIV-1 infection in the humanized mouse model leads to persistent HIV-1 infection and immunopathogenesis, including type I interferons (IFN-I) induction, immune-activation and depletion of human leukocytes, including CD4 T cells. We developed a monoclonal antibody that specifically depletes human pDC in all lymphoid organs in humanized mice. When pDC were depleted prior to HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
111
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 93 publications
(124 citation statements)
references
References 75 publications
6
111
1
2
Order By: Relevance
“…We have recently reported that pDCs play a pathogenic role in HIV-1 infection and pathogenesis (28). We also demonstrated the role of human pDCs in HIV-1-induced depletion of ILC3s.…”
Section: Figure 5 Depletion Of Pdcs Increases Hiv-1 Replication Butsupporting
confidence: 52%
See 3 more Smart Citations
“…We have recently reported that pDCs play a pathogenic role in HIV-1 infection and pathogenesis (28). We also demonstrated the role of human pDCs in HIV-1-induced depletion of ILC3s.…”
Section: Figure 5 Depletion Of Pdcs Increases Hiv-1 Replication Butsupporting
confidence: 52%
“…We recently reported that depletion of pDCs using the anti-blood dendritic cell antigen-2 (anti-BDCA2) Ab (15B) in NRG-hu mice led to elevated HIV-1 replication, but with reduced immunopathogenesis (28). In humanized mice with persistent HIV-1 infection, we detected high levels of plasma IFN-α, although pDC levels were reduced in the spleen ( Figure 5A).…”
Section: The Depletion Of Ilc3s By Hiv-1 Infection Is Dependent On Pdmentioning
confidence: 80%
See 2 more Smart Citations
“…In HIV and SIV infection, persistent high-level IFN production is associated with chronic immune activation, including higher levels of activation molecule expression, increased immune activation gene expression, and/or more rapid CD4 depletion (4,5). Increased circulating IFN during the chronic stage of HIV infection has been associated with rapid progression to AIDS (6,7).…”
Section: Introductionmentioning
confidence: 99%